2014
DOI: 10.1186/1471-2164-15-551
|View full text |Cite
|
Sign up to set email alerts
|

Quack leptin

Abstract: BackgroundA LEP transcript up-regulated in lungs of ducks (Anas platyrhynchos) infected by avian influenza A virus was recently described in the Nature Genetics manuscript that reported the duck genome. In vertebrates, LEP gene symbol is reserved for leptin, the key regulator of energy balance in mammals.ResultsLaunching an extensive search for this gene in the genome data that was submitted to the public databases along with duck genome manuscript and extending this search to all avian genomes in the whole-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Peripheral administration of leptin to obese mice induces CART mRNA expression, while CART mRNA is almost absent in the arcuate nucleus of leptin-deficient ( ob ) mice or leptin receptor ( fa )-deficient rats [ 5 ]. Recently, the authentic leptin ( ob ) gene has been identified in several birds, including zebra finches and pigeons by our and other laboratories [ 63 67 ]. Interestingly, we noted that avian leptin mRNA is predominantly expressed in the brain and pituitary, but undetectable in peripheral tissues including adipose tissue [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral administration of leptin to obese mice induces CART mRNA expression, while CART mRNA is almost absent in the arcuate nucleus of leptin-deficient ( ob ) mice or leptin receptor ( fa )-deficient rats [ 5 ]. Recently, the authentic leptin ( ob ) gene has been identified in several birds, including zebra finches and pigeons by our and other laboratories [ 63 67 ]. Interestingly, we noted that avian leptin mRNA is predominantly expressed in the brain and pituitary, but undetectable in peripheral tissues including adipose tissue [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, the key adipokine in the endocrine activity of the fat tissue in mammals, has only recently been identified and characterized in birds [ 15 18 ] and its expression was detected in a variety of tissues, but with apparent insignificant expression in the adipose tissue [ 15 , 16 , 18 ]. We also recently identified an additional key adipokine, TNF (also called TNF-α ), previously missing in chicken [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, it is in a tail-to-tail orientation (3′ to 3′; e.g. peregrine falcon, Falco peregrinus [ 23 , 24 ]; fugu, Takifugu rubripes [GenBank Gene ID: 548,631]; green sea turtle, Chelonia mydas [GenBank Gene ID: 102,932,266]; and mouse, Mus musculus [GenBank Gene ID: 16,846]). Moreover, we have previously shown that leptin is very closely linked to RBM28 in peregrine falcon and fugu (1.8 and 0.4 kbp, respectively [ 23 ]).…”
Section: Resultsmentioning
confidence: 99%
“…peregrine falcon, Falco peregrinus [ 23 , 24 ]; fugu, Takifugu rubripes [GenBank Gene ID: 548,631]; green sea turtle, Chelonia mydas [GenBank Gene ID: 102,932,266]; and mouse, Mus musculus [GenBank Gene ID: 16,846]). Moreover, we have previously shown that leptin is very closely linked to RBM28 in peregrine falcon and fugu (1.8 and 0.4 kbp, respectively [ 23 ]). Since such close proximity and the conserved 3′ to 3′ orientation suggest a local regulation of transcription [ 25 ], we further characterized RBM28 and its expression pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation